Quantitative evaluation of early retinal changes in children with type 1 diabetes mellitus without retinopathy. (28th February 2018) - Tekin, Kemal; Inanc, Merve; Kurnaz, Erdal; Bayramoglu, Elvan; Aydemir, Emre; Koc, Mustafa; Kiziltoprak, Hasan; Aycan, Zehra
Abstract : Background: To investigate whether abnormal glucose metabolism and duration of diabetes mellitus (DM) caused the thinning in retinal layers in children with type 1 DM without retinopathy by using spectral domain optical coherence tomography (SD‐OCT) and to compare the results obtained with those in healthy children. Methods: This cross‐sectional prospective study included 73 patients with type 1 DM (DM group) and 62 age‐matched control subjects (control group). The duration of DM and the glycosylated haemoglobin (HbA1c) levels of the diabetic children were recorded. Macular and peripapillary retinal nerve fibre layer (RNFL) thickness measurements obtained by SD‐OCT were compared. Results: There were significant differences in the mean values of the temporal inner, temporal outer and inferior outer macular thickness measurements between the groups (p = 0.031, p = 0.028 and p = 0.039, respectively). Moreover, the children with type 1 DM showed significantly thinner global, temporal superior and nasal inferior RNFL thickness measurements compared to the controls (p = 0.035, p = 0.022 and p = 0.034, respectively). Additionally, both the mean duration of DM and the mean HbA1c values were inversely and statistically significantly correlated with the mean temporal outer macular thickness and global RNFL thickness measurements in the DM group. Conclusions: Retinal neural changes, which can be shown by SD‐OCT, may be present in diabetic eyes even before clinically detectable retinal vasculopathy. Macular and RNFL thickness measurements might be useful indicators for early detection of diabetic retinopathy in the future.